تأمين الطلب على الطاقة الكهربائية من خلال الإدارة المثلى للحمولات الكهربائية - اسبر جورج; حمندوش عمر; الجربوع أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
تم تطبيق منهجية علمية دقيقة لدراسة الطلب على الطاقة في أنظمة عمل الشبكات الكهربائية بهدف تقليل الهدر الحاصل في الاستهلاك الكهربائي غير المنظم. حيث قمنا بدراسة الشركة العربية لصناعة أسمنت بحلب كمثال نموذجي دراسة كهربائية واقعية و ميدانية من خلال التعرف على التجهيزات الكهربائية /المحركات/ في أقسام المعمل واستطاعتها الاسمية، ثم قمنا برصد الحمولات الكهربائية لكل قسم من أقسام الشركة ورسمنا بالاعتماد على برنامج /EXEL/ منحنيات الأحمال اليومية خلال أيام معينة من السنة (2006-2005) قبل وبعد إزاحة الحمولات، وتمكنا من خلال استنباط بعض الطرق العلمية من تقليص الفارق في حمل الذروة وتقليل الهدر في الطاقة وتحسين عامل الاستطاعة للمعمل ككل. وقد بينت النتائج والحسابات الأولية بأن تطبيق هذا الإجراء العلمي الجديد يؤدي إلى خفض حمل الذروة بحدود (28 % ) على الجهد0.4kv و تحسين قيم cosφ) ) للمنشأة لتصبح ضمن الحدود المطلوبة. The research introduces a scientific accurate method to study the demand for the electrical energy in electrical function networks. The aim of the study is, on one hand, to reduce spending in the unregulated electrical consumption in both its types / home- industry / and on other hand, to lighten the load on the main electrical network, as well as to postpone building of huge generating power stations that need enormous amounts of money. This method depends on shifting some electrical loads form the peak load time to other time of day. This study was applied in the Arabian Company for Cement Industry in Aleppo city. We have already studied the company in an electrical aspect by taking some measurements of the electrical equipments / motors / in the factory’s departments, for example, the nominal power of motors, etc. Then we have achieved an observation the electrical loads of each department and drawn some graphs of daily loads using a software program /Exel/ during certain days of years /2005-2006/ before and after load shifting. So we reduced the difference in the peak load through finding out some scientific methods. As result, we could lighten the energy consumption and improve the power factor of the entire factory. The primary calculations and results show that by applying this new method, the peak load could be reduced about 28% at the 0.4kv and the power factor /cosj/ of the factory could be improved to become within the required limits.